Enabling smallholder farmers to sustainably improve their food, energy and water nexus while achieving environmental and economic benefits. (March 2020) - Gathala, Mahesh K.; Laing, Alison M.; Tiwari, T.P.; Timsina, J.; Islam, Md. S.; Chowdhury, A.K.; Chattopadhyay, C.; Singh, A.K.; Bhatt, B.P.; Shrestha, R.; Barma, N.C.D.; Rana, D.S.; et al.
Abstract: Traditional cropping practices in the Eastern Gangetic Plains, South Asia, are resource intensive, requiring large inputs of water, energy and human labor. They are also inefficient, with relatively low productivity for the inputs used although the climate, soil and water resources of the region indicate that greater productivity is achievable. In on-farm experiments conducted across three countries (Bangladesh, India, Nepal) we compared the performance of traditional and improved management practices to understand which better facilitated the production of food-grain crops while reducing energy and water demands, thus improving the sustainability of cropping system energy requirements. Benefits of improved over traditional management practices included increases of up to 10% in crop grain yields; up to 19% in water productivity; up to 26% in energy productivity; and reductions of up to 50% in labor. These metrics combined to reduce the cost of production under improved management by up to 22% and to increase gross margins by up to 100% (although in most instances gross margins increased by 12–32%). CO2 -equivalent emissions reduced by 10%–17% compared to traditional practices. The principles behind the improved management practices, which we demonstrate improve the food-energy-water nexus while concurrently promoting more sustainable use of energy resources, are applicable across smallholder farming systems throughout South Asia and in many emerging-economy countries. These improvements to traditional management practices combined with our approach of supporting farmers through the implementation of new methods has widespread applications and the potential to assist many countries transitioning to low-energy, sustainable food production. Highlights: CASI crop management practices evaluated on 436 participatory on-farm trials. CASI practices are sustainable and improve yield productivity by up to 10%. CASI reduced energy use up to 11% and improved energy productivity up to 18%. CASI reduced CO2 -equivalent emissions by up to 12%. Benefits observed for 6 common cropping systems: apply in many developing countries.